Edukasi Literasi Digital Generasi Z dalam Membangun Karakter di Era Digital di SMA Negeri 6 Palu - Husain , Sulfitri; Priskilla, Reyva Alviona; Pradana, Angga; Monggilo, Dwi Maya Loka Zainuddin; Oktaviani, Faradila; Irgi, Mohammad (Ethics and Law Journal: Business and Notary, 2026)
This study examines the law-and-economics implications of Indonesia’s minimum investment threshold regulation for foreign direct investment (FDI) and its relationship with tax base erosion risks within the evolving global fiscal governance framework. The minimum investment policy under Government Regulation No. 5 of 2021 and BKPM Regulation No. 4 of 2021 aims to enhance investment quality and safeguard national economic interests; however, administrative-oriented compliance without substantive economic presence may create structural opportunities for corporate restructuring and Base Erosion and Profit Shifting (BEPS) practices. Employing a normative juridical methodology with statutory, conceptual, and comparative approaches, supported by secondary data from BKPM, the Directorate General of Taxes, and OECD frameworks, this research finds that minimum investment regulation constitutes a legitimate exercise of the state’s right to regulate under international investment law. Nevertheless, fragmented institutional coordination between investment and tax authorities generates regulatory arbitrage risks and cross-border profit shifting. The study highlights the need for integrated governance between investment and tax regimes, substance-over-form enforcement, and alignment with the Global Minimum Tax framework to strengthen fiscal sovereignty and equitable tax outcomes Abstrak Penelitian ini menganalisis implikasi hukum ekonomi dari pengaturan nilai investasi minimum Penanaman Modal Asing (PMA) terhadap risiko erosi basis pajak di Indonesia dalam konteks reformasi tata kelola fiskal global. Kebijakan nilai investasi minimum yang diatur dalam PP No. 5 Tahun 2021 dan Peraturan BKPM No. 4 Tahun 2021 bertujuan meningkatkan kualitas investasi dan menjaga kepentingan ekonomi nasional, namun berpotensi menciptakan celah strukturisasi korporasi dan praktik Base Erosion and Profit Shifting (BEPS) apabila implementasinya lebih berorientasi administratif dibanding substansi ekonomi riil. Penelitian menggunakan metode yuridis-normatif dengan pendekatan perundang-undangan, konseptual, dan komparatif, didukung data sekunder dari BKPM, Direktorat Jenderal Pajak, dan OECD. Hasil penelitian menunjukkan bahwa kebijakan nilai investasi minimum merupakan manifestasi hak negara untuk mengatur (right to regulate), tetapi lemahnya koordinasi antara otoritas investasi dan perpajakan membuka peluang regulatory arbitrage dan profit shifting lintas yurisdiksi. Studi ini menegaskan pentingnya harmonisasi rezim hukum investasi dan perpajakan melalui integrasi kelembagaan, penerapan prinsip substance over form, serta sinkronisasi dengan kebijakan Pajak Minimum Global untuk memperkuat kedaulatan fiskal dan keadilan pajak. Kata kunci: Penanaman Modal Asing, Nilai Investasi Minimum, Erosi Basis Pajak, BEPS, Pajak Minimum Global.